2014
DOI: 10.1016/j.jad.2014.07.017
|View full text |Cite
|
Sign up to set email alerts
|

“Someone like us”: Delivering maternal mental health through peers in two South Asian contexts

Abstract: BACKGROUND Peer-led psychosocial interventions are one solution to address the great paucity of skilled mental health human resources in South Asia. The aim of this study was to explore peer-delivered care for maternal depression in two diverse contexts in South Asia. METHODS The study was carried out in the urban setting of Goa, India and a rural setting in Rawalpindi, Pakistan. In total, 61 in-depth interviews (IDIs) and 3 focus group discussions (FGDs), and 38 IDIs and 10 FGDs, were conducted with multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 32 publications
4
67
0
Order By: Relevance
“…The selection of this type of NSP reflects attempts to utilize local, affordable, and sustainable resources (Fairburn & Patel 2014); the pragmatic considerations inherent to the goal of integrating mental health care into primary care (Patel et al 2010); and community attitudes regarding preferred and accepted providers (Singla et al 2014a). Mental health specialists had diverse roles related to building competency, maintaining quality, assuring safety, and (as researchers) evaluating psychological treatments.…”
Section: Discussionmentioning
confidence: 99%
“…The selection of this type of NSP reflects attempts to utilize local, affordable, and sustainable resources (Fairburn & Patel 2014); the pragmatic considerations inherent to the goal of integrating mental health care into primary care (Patel et al 2010); and community attitudes regarding preferred and accepted providers (Singla et al 2014a). Mental health specialists had diverse roles related to building competency, maintaining quality, assuring safety, and (as researchers) evaluating psychological treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Incentives for women living in urban Goa were financial rewards compared to rural Rawalpindi where altruistic motives were of greater importance. 15 Evidence shows that the type of remuneration is indeed context-specific and has implications for the acceptability and sustainability of the intervention, and its scaling up. 28 Second, we observed that the reduction in symptom severity was greatest within the first 3 months post-childbirth.…”
Section: Discussionmentioning
confidence: 99%
“…THPP was developed during a two-year formative research phase. 11,15 Two major adaptations, related to the content and delivery mechanism, were made to the original THP intervention to make it deliverable by peers. Firstly, we shifted the focus from CBT (the active ingredient of the original THP intervention) to behavioural activation, because formative research indicated that CBT is more difficult for lay providers such as peers to learn.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations